2007
DOI: 10.1111/j.1745-4549.2007.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Incubation and Fermentation of African Locust Beans (Parkia Biglobosa) in Production of "Dawadawa"

Abstract: The effect of the following incubation materials: “gmelina” (Gmelina arborea) leaves, banana (Musa sapienta) leaves, jute bag and polythene bag on the fermentation rate and acceptability of fermented African locust beans “dawadawa” was investigated. Fermentation was carried out at 30 and 35C for 72 h. Fermentation rate was determined as a function of change in pH. Samples fermented inside gmelina leaves showed the highest fermentation rate at both temperatures followed by samples from banana leaves, polythene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…This activity was also species and strain dependant, B. pumilus showing significant higher lipolytic activity than isolates of B. subtilis. In both kinema and dawadawa fermentation increase in crude fat concentration has been reported (Azokpota et al 2006;Gernah et al 2007;Sarkar et al 1994), While decreasing concentrations have been reported in ogiri and African yam bean owoh (Ogbonna et al 2001;Omafuvbe et al 2004).…”
Section: Lipidsmentioning
confidence: 91%
See 3 more Smart Citations
“…This activity was also species and strain dependant, B. pumilus showing significant higher lipolytic activity than isolates of B. subtilis. In both kinema and dawadawa fermentation increase in crude fat concentration has been reported (Azokpota et al 2006;Gernah et al 2007;Sarkar et al 1994), While decreasing concentrations have been reported in ogiri and African yam bean owoh (Ogbonna et al 2001;Omafuvbe et al 2004).…”
Section: Lipidsmentioning
confidence: 91%
“…Bacillus subtilis strains showed higher proteolytic activity than B. pumilus leading to a release of a higher quantity of amino acids. Several studies have reported increasing levels of free amino acids, non-protein and soluble nitrogen content during alkaline fermentation (Abaelu et al 1990;Azokpota et al 2006;Gernah et al 2007;Ogbonna et al 2001;Ogunshe et al 2007;Omafuvbe et al 2000;Sarkar and Tamang 1995;Terlabie et al 2006). Ouoba et al (2003b) recorded increases in the concentration of cysteine, methionine, leucine, isoleucine, tyrosine, phenylalaline and even lysine which is limiting in plant foods during soumbala fermentation.…”
Section: Proteinsmentioning
confidence: 95%
See 2 more Smart Citations
“…It is concluded that there is evidence of considerable microbial and quality diversity of Tayohounta made by different traditional processors even when using the same batch of seed kernels but different utensils and other ingredients such as plant leaf covers. Indeed, the type of leaves used for fermentation was reported to affect both the sensory and nutritional quality of dawadawa (Gernah et al, 2007). This needs further investigations.…”
Section: Functionalitymentioning
confidence: 98%